Analysis of the Impact of Covid-19 on Structuring and MSME Profits (Case Study: Drink Time Bandar Jaya Booth Stand) - Sirait, Ribka Rikita; Tarmizi, Rosmiati (FKIP Universitas Lampung, 2023)
The UMKM Booth Stand in Bandar Jaya is currently estimated to be almost 50 booth stand players who sell a variety of foods and drinks, this booth stand's stand alone using their own business capital. However, there are problems that occur from the covid-19 outbreak in 2019 to 2021, this study is to determine the difference in revenue and profit before and during covid-19. The research method used is a qualitative method, namely a method in which research data is collected from documents, records, and reports related to the problem to be solved at the same time. Data analysis techniques in this descriptive qualitative are carried out by searching and collecting data by researchers which are then arranged systematically through field notes or documentation. The results showed that the highest decline in Drink Time Booth Stand revenue in the period 2019 to 2020 occurred in August with a percentage of -0.6%. Profit in 2019 to 2020 at Drink Time Booth Stand decreased in March with a percentage of 0.03% and followed in February with a percentage of 0.06%. In order not to experience bankruptcy Stand Booth Drink Time can make business capital loans to related parties.Keywords: Covid-19, Business Actors, Revenue, ProfitDOI: http://dx.doi.org/10.23960/E3J/v6i2.224-232